PENGEMBANGAN MEDIA PEMBELAJARAN PANGGUNG SIKLUS HIDROLOGI PADA MATA PELAJARAN IPA DI KELAS V - Annisa Wijariyah; A Syachruroji; Nana Hendracipta (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to reveal how to develop the water cycle stage media for science learning at grade V, to analyze the feasibility of water cycle stage media developed for science learning at grade V, and to reveal the students’ response to the water cycle stage learning media. This study was conducted at SDN Teras 1. The subjects of this study were 20 students at grade V SDN Teras 1, in which 15 students were on a limited trial. This study was conducted based on Borg and Gall model modified by Sugiyono. This model included six stages: namely problem analysis, data collection, product design, design validation, design revision, and product testing. The instruments in this study were questionnaire sheets which were addressed for the lecturer and students. Based on the result of data analysis, it was found that the quality of the water cycle stage media was presented in three categories. First, the feasibility of water cycle media from the media experts was categorized as very feasible with a percentage of 91.3%. Then, according to the material experts, this media was alo categorized as very feasible with a percentage of 93%. Finally, the feasibility result from education experts was also categorized as very feasible with a percentage of 93%. In addition, after conducting the trial to 15 students, the result of the students’ response to the water cycle stage media was 89%, which was also in the very feasible category.